Main Exhibit Palaces (Pacific Novelty Co.)
On verso: The exposition is situated in a natural amphitheatre on the shores of the wonderful island dotted bay of San Francisco just inside the Golden Gate. There are eleven main exhibit palaces, containing examples of all the resources and achievements along all lines of human endeavor.